Antiretroviral treatment can reduce the risk of HIV transmission between male partners to 'zero'. (27th August 2019) - Cook, Rob; Davidson, Peter; ,; Martin, Rosie
The study: A Rodger, V Cambiano, T Bruun, et al. Risk of HIV transmission through condomless sex in serodifferent gay couples with the HIV-positive partner taking suppressive antiretroviral therapy (PARTNER): final results of a multicentre, prospective, observational study. Lancet 2019;393:2428-38. This project was funded by the NIHR Research for Patient Benefit Programme (project number PB-PG-1013-32069). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000785/antiretroviral-treatment-can-reduce-the-risk-of-hiv-transmission-between-male-partners-to-zero